The Relation of Kendang and Jaipongan: Functions and Inspirations of Kendang Musicality on Jaipongan’s Journey (Harmonia: Journal of Arts Research and Education, 2020)
This study aims to describe the Kendang relationship, as a traditional Priangan musical instrument, to the Jaipongan performing arts and dance. Kendang, which has a central function in the Jaipongan dance performance, has received less appreciation in West Java arts’ discourse. The Jaipongan dance art focuses on dance movements, although the song (gending) that accompanies the dance movement depends entirely on the Kendang music playing. This study used qualitative research methods. The data collection technique is done through interviews, observation, and document study. Data were analyzed through complete data collection activities and then adjusted the data and literature review, and in the end, described the research data. The results showed that Kendang, as a musical instrument has a relationship and attachment with the creation and development of the Jaipongan dance art. Kendang and the player (pengendang) have a vital function, in contrast to the stereotype that these instruments are only accompaniment to songs/dances in the performing arts. The Kendang instrument is an important part that regulates the tempo and the course of the Jaipongan dance performance. Pengendang, as artists and musicians, contribute greatly in communicating the performance of the performance both with dancers and the audience. Kendang is a source of inspiration for the creation of Jaipongan dance art. During the process of creating the Jaipongan dance, Gugum Gumbira acts as a creator communicating with other artists, both dancers, and pengendang.